2002
DOI: 10.1300/j013v36n02_07
|View full text |Cite
|
Sign up to set email alerts
|

Environmental, Policy, and Cultural Factors Related to Physical Activity in African American Women

Abstract: Six focus groups were conducted in South Carolina with African American women (n = 42) aged 19-51 years to identify factors that influence physical activity. Transcripts were analyzed using NUD*IST. Cultural influences were seen as more important in determining the type of physical activity than its level. Barriers to and enablers of physical activity were identified in the social and physical environments, as were policy issues affecting physical activity in the community and at the work site. Potential commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 7 publications
(6 reference statements)
0
73
1
Order By: Relevance
“…Our encouraging results and similar between-group attrition rates suggests that our approach was acceptable, feasible, and potentially efficacious in promoting physical activity in a low-income, underserved population known to have low intervention uptake and less successful response to physical activity and smoking interventions than the general population-major contributors to health disparities [57][58][59][60][61]. A review of counseling treatments in low-income populations underscored the need to establish enhanced interventions for this high-risk group, including more effective telephone-based counseling services (e.g., quitlines) [62].…”
Section: Discussionmentioning
confidence: 65%
“…Our encouraging results and similar between-group attrition rates suggests that our approach was acceptable, feasible, and potentially efficacious in promoting physical activity in a low-income, underserved population known to have low intervention uptake and less successful response to physical activity and smoking interventions than the general population-major contributors to health disparities [57][58][59][60][61]. A review of counseling treatments in low-income populations underscored the need to establish enhanced interventions for this high-risk group, including more effective telephone-based counseling services (e.g., quitlines) [62].…”
Section: Discussionmentioning
confidence: 65%
“…Lechner, Bolman, and Van Dijke (2005) had opined that increasing the accuracy of people's self-perceptions of physical activity may be an important strategy to promote physical activity in populations at risk of inactivity. Unfortunately, extrapolation of perceptions from studies conducted in other settings may not be entirely appropriate because of the different social and cultural backgrounds of the participants in the different studies (Richter, Wilcox, Greaney, Henderson, & Ainsworth, 2002;Eyler, Vest, & Sanderson, 2002). Ability to improve peoples' perception about physical activity will enhance behavioural change, but achieving this will only be possible if different communities assess the perceptions of their residents in order to establish whether or not they have an appropriate perception of their physical activity levels.…”
Section: Introductionmentioning
confidence: 99%
“…Low PA levels are a major factor influencing increased BMI and obesity levels among AAW in the U.S. (Kumanyika et al, 1993;Richter et al, 2002). Studies have found that obese AAW experience lower levels of general wellbeing and exercise performance (Patt et al, 2004;CDC, 2001) and these characteristics are influenced by their perceived self-efficacy (Eyler et al, 2002a).…”
Section: Behavioral Factors Physical Activitymentioning
confidence: 99%
“…Social pressures resulting from life style (i.e. time needed for work and preparation of nutritious meals) and familial responsibilities are factors influencing food preparation techniques, and eating habits; they also affect the nutritional values of many foods consumed by AAW (Baturka et al, 2000;Jefferson et al, 2010;Hargreaves et al, 2002;Richter et al, 2002).…”
Section: Nutrition and Food Preparationmentioning
confidence: 99%
See 1 more Smart Citation